Chordoma and chondrosarcoma: Similar, but quite different, skull base tumors - Almefty, Kaith; Pravdenkova, Svetlana; Colli, Benedicto O.; Al‐Mefty, Ossama; Gokden, Murat (Cancer, 2007)
BACKGROUND Chordoma and chondrosarcoma of the skull base are frequently amalgamated because of similar anatomic location, clinical presentation, and radiologic findings. The chondroid chordoma variant has been reported to carry a better prognosis. The objective of the current study was to investigate the distinctions between these 3 entities. METHODS The data concerning 109 patients with chordoma, chondroid chordoma, and chondrosarcoma who were treated by a single surgeon with maximum surgical resection and frequently by adjunct proton beam radiotherapy between 1990 and 2006 were analyzed retrospectively. Pathologic distinction was established by cytokeratin and epithelial membrane antigen staining. Clinical, radiologic, pathologic, and cytogenetic studies were analyzed in relation to disease recurrence and death. RESULTS The average follow‐up was 48 ± 37.5 months (range, 1–191 months). There were no reliable distinguishing clinical or radiologic features noted between the groups. Chondrosarcoma patients had a significantly better outcome compared with chordoma patients with regard to survival and recurrence‐free survival (P = .028 and P < .001, respectively), whereas patients with chondroid chordoma had a poor outcome similar to chordoma patients with regard to survival and recurrence‐free survival (P = .337 and P = .906, respectively). CONCLUSIONS Chordoma and chondrosarcoma differ with regard to their origin and histology, and differ markedly with regard to outcome. Chondroid chordomas behave in a manner that is clinically similar to chordomas, with the same prognosis. Both chordoma types demonstrate an aggressive clinical course and poor outcome after disease recurrence. The optimal treatment for all groups of patients involves radical surgical resection followed by high‐dose radiotherapy in patients with chordomas. Radiotherapy may not be necessary in patients with low‐grade chondrosarcoma. Cancer 2007. © 2007 American Cancer Society. Chordoma and chondrosarcoma of the skull base are frequently amalgamated because of similar anatomic location, clinical presentation, and radiologic findings. However, these tumors differ with regard to origin and histology, and differ markedly in outcome. Chondroid chordoma carries the same poor prognosis as chordoma. The optimal treatment for all groups involves radical resection followed by high‐dose radiotherapy in patients with chordoma. Radiotherapy may not be necessary in patients with low‐grade chondrosarcoma.